Answer:
B. P(-4)=-144
Step-by-step explanation:
From the question, we have that:
[tex] \frac{p(x)}{x + 4} = {x}^{2} - 7x + 34 - \frac{144}{x + 4} [/tex]
This implies that:
[tex]p(x)=(x + 4)( {x}^{2} - 7x + 34) - 144[/tex]
To find p(-4), we put x=-4
[tex]p( - 4)=( - 4+ 4)( {( - 4)}^{2} - 7 \times - 4 + 34) - 144[/tex]
[tex]p( - 4)=( 0)( {( - 4)}^{2} - 7 \times - 4 + 34) - 144 = - 144[/tex]
To find p(0), we put x=0 to get:
[tex]p( 0)=( 0+ 4)( {( 0)}^{2} - 7 \times 0+ 34) - 144[/tex]
[tex]p( 0)=(4)( 34) - 144 = - 8[/tex]
The correct answer is B